The Effects of Macroeconomic Variables, Indonesia Sharia Stock Index, and Sukuk Outstanding Value on the Net Asset Value of Islamic Mutual Funds for the 2018-2024 Period - Sulaiman; Alif Wildana, Muhammad Dandy (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The development of sharia mutual funds fluctuated from 2018 to 2024. This was influenced by various factors such as macroeconomics, the market capitalization of the Indonesian sharia stock index, and the outstanding value of sukuk. The purpose of this study was to determine the effect of inflation, BI 7 Day Repo Rate (BI7DRR), exchange rates, money supply (M2), the market capitalization of the Indonesian Sharia Stock Index (ISSI), and the outstanding value of sukuk on the net asset value (NAV) of sharia mutual funds in Indonesia in the short and long term for the period 2018-2024. This research uses a quantitative approach with the Autoregressive Distributed Lag (ARDL) analysis method using Eview 12 software. In the short term, inflation, exchange rates, and ISSI have a significant negative effect on the NAV of Islamic mutual funds. Then, the amount of money in circulation (M2) and the outstanding value of sukuk have a significant positive effect in the short and long term on the NAV of sharia mutual funds. Furthermore, BI7DRR has no effect on the NAV of sharia mutual funds. These results are expected to serve as additional reference for investors, investment managers, companies, and the government in assessing the extent to which these variables affect the NAV and in developing strategies to address them.